2019
DOI: 10.1111/fare.12353
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Work Hours and Single Versus Coupled Mothers' Work‐to‐Family Conflict

Abstract: Objective To compare single and coupled mothers' experiences of time‐based work‐to‐family conflict (WFC) and work‐to‐family positive affective spillover (PAS) in the context of maternal nonstandard work hours. Background Despite having become one of the central topics of work–family research, studies examining the relationship of maternal work schedules and family roles have mainly focused on North American samples or dual‐earner families. Although qualitative studies have highlighted the problems faced by Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
0
30
0
2
Order By: Relevance
“…Our dataset consisted solely of two-parent residential families. In our sample, therefore, parents could at least to some extent share the burden of home-schooling between them, which generally is related to lower W→F-conflict (Moilanen et al, 2019). Our findings might therefore not be generalizable to single parents, where W→F-conflict/F→W-conflict might have increased even more and the spill-over to perceived parenting might have been more difficult to prevent.…”
Section: Directions For Future Researchmentioning
confidence: 72%
“…Our dataset consisted solely of two-parent residential families. In our sample, therefore, parents could at least to some extent share the burden of home-schooling between them, which generally is related to lower W→F-conflict (Moilanen et al, 2019). Our findings might therefore not be generalizable to single parents, where W→F-conflict/F→W-conflict might have increased even more and the spill-over to perceived parenting might have been more difficult to prevent.…”
Section: Directions For Future Researchmentioning
confidence: 72%
“…Usdansky, 2011), household composition (e.g. Moilanen et al, 2019) and sexuality (Duncan et al, 2003). Examining the renegotiation process when household routines are disrupted, as in the case here of redundancy, across diverse household forms would provide a fruitful avenue for future research.…”
Section: Resultsmentioning
confidence: 99%
“…hours. Yet, the excusing accounts showed that these were not feasible options because of the financial pressure in which many of the mothers found themselves as sole earners (see Mukkila et al, 2017;Roman, 2018) and the relative lack of jobs offering standard hours. Instead, the mothers relied on their personal resources (e.g., sleep, time) and adaptability in responding appropriately to the needs of their children, on their social support networks (see Alsarve, 2017; Roman, 2018) and on negotiating flexible hours with their employers in striving to protect child wellbeing while having to work non-standard hours.…”
Section: Discussionmentioning
confidence: 99%
“…The moral dilemmas experienced by working lone mothers, we argue, have been intensified by the demands of the contemporary labour market. The working time demands characteristic of the 24/7 economy, especially non-standard working hours taking place during early mornings, evenings, nights, and weekends (Presser, 2003), have complicated the challenges that mothers face in reconciling work and family (e.g., Moilanen et al, 2019). Non-standard working hours are common, for example, in the female-dominated service and health sectors characterized by shift work (Parent-Thirion et al, 2007).…”
Section: Moral Order Fragmented -Standard Hoursmentioning
confidence: 99%